PENGARUH KERJA PARUH WAKTU, MOTIVASI BELAJAR DAN TIME MANAGEMENT TERHADAP PRESTASI AKADEMIK: STUDI KASUS PADA MAHASISWA YANG SEDANG BEKERJA PART TIME - Alya Agustina; Ahmad Mardalis (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the effect of part-time work, learning motivation and time management on academic achievement (case study on students who are working part-time). This research method is quantitative. The population of this study is students who are working part-time. The sample size of this study was 250 respondents. The sampling technique uses a non-probability sampling approach  with purposive sampling techniques. The type of data used in this study is primary data. The data collection technique used in this study was a questionnaire. The data analysis technique in this study uses Partial Least Square (PLS). The statistical software used to analyze the data is SmartPLS version 3. The result of this study is that working part-time has a positive and significant effect on academic achievement. Learning motivation has a positive and significant effect on academic achievement. Time management has a positive and significant effect on academic achievement